To study the knowledge, attitude and practice of breastfeeding among postnatal mothers in a tertiary care center of South India - Rudrappa, Sudha; Raju, Hunasagahally Nagaraju Yashwanth; Kavya, Mukkanara Yathiraju (Indian Journal of Child Health, 2020)
Background: Breastfeeding is physiological and ideal way of feeding the infants. It offers complete nutrition, early protection against illness, and promotes growth and development of the infant. Objectives: The objectives of the study were to study the knowledge, attitude, and practice of breastfeeding among postnatal mothers and to study the demographic and socio-economic factors associated with breastfeeding practices. Materials and Methods: The present study was a cross-sectional study conducted at postnatal wards of a tertiary hospital of South India between October and November 2018. A total of 200 mothers in the postnatal wards were included in the study. Knowledge and attitude of the mothers was assessed using a scoring system. Socio-demographic data, antenatal care of mother, birth history, and breastfeeding details were used as domains of study. Data were analyzed using SPSS software version 20.0. Results: Majority (60%) of the mothers belonged to 15–25 years age group. A total of 20% of the mothers in the present study were illiterate, 51.5% of mothers were homemakers, 68% belonged to nuclear family, and 74% belonged to urban population. Among 200 postnatal mothers, 90% who delivered vaginally had knowledge regarding time of initiation of breastfeeding, 70% had knowledge regarding colostrums feeds, and 35% had knowledge regarding duration of exclusive breastfeeding. Conclusion: Mothers had an average knowledge regarding breastfeeding at our center. There is a need to strengthen public health education system to promote breastfeeding. Age, education, occupation, economic status, religion, and type of family were found to be significant associates of their knowledge and attitude.